Assessing the sustainability and resilience of cacao-cased farming systems in Pili, Camarines Sur, the Philippines - Nurul Amri Komarudin; Eaint Thet Wai; Nusron Habibur Rohman; Leah Endonela (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2025)
Camarines Sur, located in the Bicol Region of the Philippines, is considered one of the most climate-vulnerable provinces. Despite this, it is a model for a robust and proactive disaster risk reduction and management (DRRM) program. The province features a diverse agroecological landscape, ranging from hilly and rolling terrains to plains surrounding Mt. Isarog National Park, which covers an area of 10.112 hectares with an elevation reaching 1.966 meters above sea level. Farming systems include monocropping, intensive multiple cropping, and agroforestry, with sugarcane and corn on downslopes, groundnuts and vegetables on lower slopes, and irrigated or rainfed rice fields. The integration of cacao (Theobroma cacao L.) is increasingly being explored as a means to enhance both the sustainability and resilience of these farming systems. This study aims to assess the sustainability and resilience of cacao cultivation at the farm level in Barangay Binanuanan, Pili, Camarines Sur. A qualitative research design was employed, utilizing semi-structured interviews with local government officials, focus group discussions with farmers, and a Strengths, Opportunities, and Challenges (SOC) analysis. Findings indicate that cacao farming contributes to economic sustainability, as most farmers benefit from diversified income sources, including off-farm employment and family financial support. Ecological sustainability is supported by cacao’s compatibility with existing farming practices. However, social resilience remains limited, as evidenced by the aging farming population and minimal youth engagement in agriculture. To strengthen overall system resilience, targeted interventions promoting youth participation and community engagement in cacao-based farming are recommended.